Risk of Diversion in Lending as One of the Corruption Crimes at BUMN / BUMD Banks - Indra Gunawan Purba (SIASAT, 2021)
Abuse in granting credit is prohibited binding because the misappropriation is an act that is against the law (statutory regulation) so that it is an act against the law. The act of deviating from the provision of credit is an act that is detrimental to the bank and the general public, because the function of the bank is to drive the community's economy. If the bank is poorly managed and has the potential to cause chaos to the economy in a country. Regarding the management of BUMN / BUMD banks whose capital is from the APBN and APBD which are state money, the act of misappropriation in providing credit to BUMN / BUMD banks has the potential to cause losses to state finances. So that non-creditors qualify as criminal acts of corruption.